The impact of internal and external factors on human rights conditions in Xinjiang, China - Rogers, Roy Anthony (College of Law, Government and International Studies, Universiti Utara Malaysia., 2010)
In 1949, the Chinese Communist Party (CCP) took control of Xinjiang from the Koumintang (KMT) and declared that Xinjiang was to be an autonomous region in 1955. However, major decisions were still made by the CCP led by the Han Chinese and not the Uyghurs from Xinjiang. The CCP implemented aggressive assimilation policies in the 1960s especially during the Cultural Revolution during which the Uyghurs were subjected to serious abuses. In 1978, Deng Xiaoping took over the leadership of China after the demise of Mao Zedong. It brought about dramatic changes in the human rights situation in China. These included freedom for the Uyghurs to practice their religion, culture and language. Hence, there was an improvement in human rights in Xinjiang. However, in the late 1990s the CCP reverted to harsh policies once again. This study examines the internal and external factors that have influenced China's policies on the human rights condition in Xinjiang. The aim of this study is to analyse the changes in the human rights condition in Xinjiang under the different administrations and the factors that have caused the changes.